2020
DOI: 10.1007/s10557-020-07073-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on the Cardiovascular System: A Review of Available Reports

Abstract: The recent emergence of the coronavirus disease 19 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in China is now a global health emergency. The transmission of SARS-CoV-2 is mainly via human-to-human contact. This virus is expected to be of zoonotic origin and has a high genome identity to that of bat derived SARS-like coronavirus. Various stringent measures have been implemented to lower person-to-person transmission of COVID-19. Particular observations and attempts have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
67
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 147 publications
0
67
0
1
Order By: Relevance
“…Understanding the risk factors for cardiac involvement in COVID-19 infection is important; previous reports have found an increase in mortality of infections that are associated with cardiac injury ( 15 , 16 ). It has been reported that risk factors for cardiac-specific involvement from established COVID-19 infection include many of the aforementioned risk factors for bad outcomes, including DM, HTN, chronic heart failure, previous CAD, atherosclerotic heart disease, and even cancer ( 11 ).…”
Section: Risk Factors Of Cardiovascular Involvement In Covid-19 Infecmentioning
confidence: 99%
See 4 more Smart Citations
“…Understanding the risk factors for cardiac involvement in COVID-19 infection is important; previous reports have found an increase in mortality of infections that are associated with cardiac injury ( 15 , 16 ). It has been reported that risk factors for cardiac-specific involvement from established COVID-19 infection include many of the aforementioned risk factors for bad outcomes, including DM, HTN, chronic heart failure, previous CAD, atherosclerotic heart disease, and even cancer ( 11 ).…”
Section: Risk Factors Of Cardiovascular Involvement In Covid-19 Infecmentioning
confidence: 99%
“…Notable laboratory findings have also been associated with increased cardiovascular involvement during infection. D-dimer elevation of patients was linked with increased hospital death, associating hypercoagulation states from SARS-CoV-2 with elevated inflammatory responses to the virus ( 3 , 15 ). In a Chinese cohort, increased levels of NT-proBNP was associated with a need for ICU care, linking heart failure-associated ACE2 upregulation with COVID-19 infection and severity ( 3 ).Elevated levels of troponin I, CRP, ferritin, IL-6, IL-1β, and IFN-γ during cytokine storms can be a predictor of severity of COVID-19.…”
Section: Risk Factors Of Cardiovascular Involvement In Covid-19 Infecmentioning
confidence: 99%
See 3 more Smart Citations